Bridging law shape for long fibre composites and its finite element construction - Kozák, Vladislav; Chlup, Zdenek (Proceedings of the Conference Algoritmy, 2015)
Ceramic matrix composites reinforced by unidirectional long bres are very perspective materials. Especially glass matrix composites reinforced by unidirectional long ceramic bres are very complicated materials for modelling thanks their common acting of various micromechanisms like pull out, crack bridging, matrix cracking etc. Crack extension is simulated by means of element extinction algorithms. The principal eort is concentrated on the application of the cohesive zone model with the special traction separation law (bridging). Determination of micro-mechanical parameters is based on the combination of static tests, microscopic observation and numerical calibration procedures. The paper is oriented to the construction of the new type of element for FEM program (Abaqus).